Social Acceptance of Green Electricity: A Case Study in Putrajaya - Azizan, Suzana Ariff; Ahmad Sayuty , Ahmad Nazirul Akmal (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2022)
In recent years, the majority of the renewable energy programmes and initiatives introduced have been industry and commercial centric. Little focus has been given by the government to domestic consumers’ acceptance. The concept of "social acceptance" is used to evaluate the readiness of the public in embracing renewable investments within their area. It is a tool to measure the attitude of citizens, either active or passive, towards different green products or technologies. This study aims to identify factors that influence the social acceptance of green electricity among consumers and, subsequently, the relationship between these factors. An empirical study was conducted on the residents of Putrajaya, involving 185 respondents. Descriptive analysis and Pearson correlation were used as analysis methods in this study. The results showed that attractiveness, compatibility, and reliability are the main factors that influence their intention to use green electricity. These results suggest that the respondents’ intention to use green electricity is not affected by their level of environmental knowledge or the cost of using green electricity.